“But how could anyone rationalize policies that discriminate?: Understanding Canada’s Failure to Implement Jordan’s Principle - King, Jennifer (First Peoples Child & Family Review, 2012)
This article seeks to understand Canada’s failure to implement Jordan’s Principle, a child-first policy ensuring First Nations have access to the same level and quality of services available to other children. Policy-making in Canada rests firmly within a neoliberal political framework that extends market-based thinking to all aspects of social life. Neoliberal thought interlocks with stories of Other to inform notions of deservingness as well as one’s potential as a valuable citizen with something to contribute. Social policy decisions, including the decision to implement a particular policy or not, offer a means through which to disseminate neoliberal values and norms. As self-determining peoples with distinct rights, lands, and governance structures, First Nations transgress the image of the “good” neoliberal citizen in a variety of ways. Neoliberalism holds that punitive measures are sometimes needed to encourage citizens to adopt particular norms, and this allows policy makers to rationalize and justify policies that discriminate against First Nations children. Stereotypes about Indigenous peoples are also used to manipulate public sentiment in favour of government policy. Canada’s failure to implement Jordan’s Principle can be understood as part of a broader strategy to encourage First Nations to rescind their distinct rights and assimilate as good neoliberal citizens.